2017
DOI: 10.24154/jhs.v12i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated nutrient management on dry herbage yield, nutrient uptake and profitability of French Basil (Ocimum basilicum L.)

Baraa AL Mansour,
Kalaivanan D,
Suryanarayana M A
et al.

Abstract: Field experiments were conducted at ICAR - Indian Institute of Horticultural Research, Bengaluru during Kharif season of 2015 and 2016 with nine treatments and three replications in a randomized block design to find out the effect of integrated nutrient management on dry herbage yield, nutrient uptake and economics of sweet basil (Ocimum basilicum). The results revealed that the conjunctive use of inorganic fertilizer along with FYM increased the dry herbage yield and nutrient uptake of sweet basil. Applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, several other studies in medicinal and aromatic plant species clearly showed that the combined application of organic and inorganic fertilizer reveals enhanced essential oil content and yield in Lamiaceae family [ 40 , 48 ]. The nitrogen and phosphorous supplied by the different fertilizers play an important role in formation of ATP and NADPH that ultimately act as a key component in synthesis of several secondary metabolite compounds [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, several other studies in medicinal and aromatic plant species clearly showed that the combined application of organic and inorganic fertilizer reveals enhanced essential oil content and yield in Lamiaceae family [ 40 , 48 ]. The nitrogen and phosphorous supplied by the different fertilizers play an important role in formation of ATP and NADPH that ultimately act as a key component in synthesis of several secondary metabolite compounds [ 49 ].…”
Section: Resultsmentioning
confidence: 99%